Emergence of Staphylococcus aureus Carrying Multiple Drug Resistance Genes on a Plasmid Encoding Exfoliative Toxin B - Hisatsune, Junzo (American Society for Microbiology, 2013)
We report the complete nucleotide sequence and analysis of pETB(TY825), a Staphylococcus aureus TY825 plasmid encoding exfoliative toxin B (ETB). S. aureus TY825 is a clinical isolate obtained from an impetigo patient in 2002. The size of pETB(TY825), 60.6 kbp, was unexpectedly larger than that of the archetype pETB(TY4) (∼30 kbp). Genomic comparison of the plasmids shows that pETB(TY825) has the archetype pETB(TY4) as the backbone and has a single large extra DNA region of 22.4 kbp. The extra DNA region contains genes for resistance to aminoglycoside [aac(6′)/aph(2″)], macrolide (msrA), and penicillin (blaZ). A plasmid deletion experiment indicated that these three resistance elements were functionally active. We retrospectively examined the resistance profile of the clinical ETB-producing S. aureus strains isolated in 1977 to 2007 using a MIC determination with gentamicin (GM), arbekacin (ABK), and erythromycin (EM) and by PCR analyses for aac(6′)/aph(2″) and msrA using purified plasmid preparations. The ETB-producing S. aureus strains began to display high resistance to GM, which was parallel with the detection of aac(6′)/aph(2″) and mecA, after 1990. Conversely, there was no significant change in the ABK MIC during the testing period, although it had a tendency to slightly increase. After 2001, isolates resistant to EM significantly increased; however, msrA was hardly detected in ETB-producing S. aureus strains, and only five isolates were positive for both aac(6′)/aph(2″) and msrA. In this study, we report the emergence of a fusion plasmid carrying the toxin gene etb and drug resistance genes. Prevalence of the pETB(TY825) carrier may further increase the clinical threat, since ETB-producing S. aureus is closely related to more severe impetigo or staphylococcal scalded-skin syndrome (SSSS), which requires a general antimicrobial treatment.